29 SIGLEC-1 (CD169) on monocytes/macrophages: a new receptor for extracellular self-RNA in triggering inflammatory responses via the sheddase TACE/ADAM17. (17th November 2015) - Cabrera-Fuentes, HA; Preissner, KT; Boisvert, WA
Abstract : As an important component of atherosclerosis, monocytes/macrophages respond to external stimuli with rapid changes in their expression of many inflammation-related genes to undergo polarisation towards the M1 (pro-inflammatory) or M2 (anti-inflammatory) phenotype. Although sialoadhesin (Sn), also known as SIGLEC-1 or CD169, is a transmembrane protein receptor expressed on monocytes and macrophages whether it has a role in macrophage polarisation and ultimately, macrophage-driven atherogenesis, has not been investigated. We have previously shown that, extracellular-RNA (eRNA) could exert pro-thrombotic and pro-inflammatory properties in the cardiovascular system by inducing cytokine mobilisation. In the current study, recombinant mouse macrophage CSF–driven bone marrow-derived macrophage (BMDM) differentiation was found to be skewed towards the M1 phenotype by exposure of cells to eRNA. This resulted in up-regulation of inflammatory markers, whereas anti-inflammatory genes were significantly down-regulated by eRNA. Interestingly, eRNA was released from BMDM under hypoxia and induced TNF-α liberation by activating TNF-α converting enzyme (TACE) to provoke inflammation. Murine BMDM isolated from mice deficient in sialoadhesin had the opposite reaction to eRNA treatment with a prominent down-regulation of pro-inflammatory cytokines/M1 phenotype markers, while anti-inflammatory cytokines/M2 phenotype markers were significantly raised. In keeping with the proposed role of eRNA as a pro-inflammatory "alarm signal", these data further shed light on the role of eRNA in macrophage function in the context of chronic inflammatory diseases such as atherosclerosis. The identification of sialoadhesin as putative eRNA recognition site on macrophages may allow further investigation of the underlying mechanisms of eRNA-macrophage interaction and related signal transduction pathways.